2020
DOI: 10.7759/cureus.11328
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anesthetic Variation in Endovascular Treatment of Acute Ischemic Stroke

Abstract: Background Given recent technological advancements leading to better outcomes in endovascular therapy for acute ischemic stroke (AIS), updated guidelines recommend thrombectomy as the standard of care in acute large vessel occlusions. However, use of general anesthesia versus conscious sedation continues to be discussed. Two previous randomized trials have shown no significant difference between the use of conscious sedation compared with general anesthesia. Methods The authors performed a retrospective analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Concerning an association of general anesthesia with time taken for revascularization, several studies have reported conflicting results. Recently, Salehani et al 24 reported a shorted revascularization time in patients who underwent thrombectomy under conscious sedation as opposed to general anesthesia; however, the difference was not statistically significant. 24 A meta-analyses by Campbell et al 25 showed that general anesthesia was associated with significantly prolonged randomization to revascularization time as compared to the conscious sedation group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Concerning an association of general anesthesia with time taken for revascularization, several studies have reported conflicting results. Recently, Salehani et al 24 reported a shorted revascularization time in patients who underwent thrombectomy under conscious sedation as opposed to general anesthesia; however, the difference was not statistically significant. 24 A meta-analyses by Campbell et al 25 showed that general anesthesia was associated with significantly prolonged randomization to revascularization time as compared to the conscious sedation group.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Salehani et al 24 reported a shorted revascularization time in patients who underwent thrombectomy under conscious sedation as opposed to general anesthesia; however, the difference was not statistically significant. 24 A meta-analyses by Campbell et al 25 showed that general anesthesia was associated with significantly prolonged randomization to revascularization time as compared to the conscious sedation group. Further, the clinical outcomes at 3 months were significantly better in those who underwent endovascular procedure under conscious sedation.…”
Section: Discussionmentioning
confidence: 97%
“…Historically, approximately half of the thrombectomies performed at our institution are done under conscious sedation rather than general anesthesia, with no apparent implications on discharge disposition or mortality rates. 16 When GA is employed, our pre-pandemic protocol involves intubation in the angiography suite by the anesthesia team, rather than in the emergency department by an emergency medicine physician.…”
Section: Methodsmentioning
confidence: 99%